Use of Bovine Pericardium and Sutureless Biological Glue in Left Ventricular Rupture After Mitral Valve Replacement, Five Years of Follow-up - Costa,Mário Augusto Cray da (2015)
ABSTRACT Rupture of the left ventricular wall after mitral valve replacement is an infrequent but lethal complication. Reporting correction technique of ventricular rupture with bovine pericardium patch secured with glue and without suturing: a 51 years-old female patient, with double rheumatic mitral lesion, severe stenosis and discrete insufficiency, who had a mitral valve replacement. During surgery, the patient presented a ventricular rupture of the posterior wall (atrioventricular disruption), which was successfully repaired using bovine pericardium with sutureless biological glue over the epicardium of the damaged area. Sixty months after surgery the patient has no symptoms.